Strategi Coping (Problem Focused Coping dan Emotion Focused Coping) Dalam Menghadapi Stres Pada Mahasiswa Penyusun Skripsi FKIP Universitas Syiah Kuala. - Nauratul Iqramah; Nurhasanah Nurhasanah; Nurbaity Bustamam (JIMBK: Jurnal Ilmiah Mahasiswa Bimbingan & Konseling, 2018)
This research entitled "Coping Strategy (Problem Focused Coping and Emotion Focused Coping) in Facing Stress on Student Composer of FKIP Universitas Syiah Kuala". The purpose of this study is to determine the level of stress and coping strategies used by students in dealing with stress when preparing the thesis. This research uses quantitative approach implemented in Faculty of Teacher Training and Education (FKIP) with sampling using accindental sampling technique. Sample research used is the students who are preparing a thesis as many as 100 people who meet the requirements and criteria specified by researchers. Data collection using questionnaires namely the stress level questionnaire and also questionnaire coping strategies are processed with descriptive statistical analysis. After doing the data processing, the first questionnaire obtained the description of stress level of students who made the thesis is 72% are in the medium category, 19% are in the high category and 9% are in the low category. Furthermore, in the second questionnaire to find coping strategies used by students in dealing with stress, it was found that most students in facing stress using problem focused coping strategy that is as much as 56% and 44% using coping emotion focused coping strategy. The conclusion in this research shows that most of the students who make the thesis experience stress in the medium category and face the stress by using different coping strategies. Based on these results, the researcher suggested to the students to use effective coping strategies such as raising awareness of the problem, pengelohan information and behavior change in facing stress when preparing the thesis.